Hiding in the spotlight : a musical prodigy's story of survival, 1941-1946 - Dawson, Greg. (New York : Pegasus Books, 2009)
The author relates the story of his pianist mother, a child prodigy who escaped certain death when the Nazis invaded Ukraine, adopted a new identity, and came under the protection of a Nazi commander who heard her play.
Includes bibliographical references (p. 273-274)
Keywords: Arshanskaya, Zhanna -- Childhood and youth; Pianists -- Biography; Gifted children -- Biography; World War, 1939-1945 -- Children -- Ukraine -- Biography; World War, 1939-1945 -- Ukraine -- Biography; Holocaust, Jewish (1939-1945) -- Ukraine -- Biography